Challenges of teaching economics in Ebonyi State - Ukoro, Anthonia Chukwu; Ifere, Paul Ikechukwu; Chuks-Ezekwibe, Ogechukwu M.; Okoche, Prince Emmanuel (Journal of Professional Secretaries and Office Administrators, 2022)
Challenges of teaching economics in Ebonyi State